Management of Stress and Functional Neurological Symptom Disorder through Hypnosis - Aisha, Kiran (2024)
Stress and Functional Neurological Symptom Disorder (FNSD) both have the potential to seriously lower someone's quality of life. As a therapeutic method, hypnosis is a potential way to reduce stress and the symptoms related to FND. The study seeks to evaluate the potential benefits of hypnosis-based interventions in treating symptoms of stress and FNSD. This study also develop and a reliable and valid instrument that can accurately measure the symptoms and severity of FNSD in patients using pilot study. The study was a mix method research design was used in this study. The quantitative phase involved 180 patients diagnosed with FNSD, where the HSS and DASS were used to measure outcomes. Statistical analysis, including Pearson correlation, one-way ANOVA, and non-parametric t-tests, indicated significant improvements in stress levels and FNSD symptoms post-intervention, with hypnosis showing a notable predictive value for symptom reduction. The quantitative data demonstrate significant correlations and predictive values for hypnosis in reducing stress and FNS symptoms. The qualitative phase included in-depth interviews with 20 participants, analyzed through thematic analysis. Themes emerged around the impact of significant life events, relationships between emotional and physical symptoms, the role of support systems, and the perceived effectiveness and comfort of hypnosis as a therapeutic approach. Participants reported a strong sense of safety and control during hypnosis sessions, which facilitated positive psychological and physiological outcomes. The combined findings from both quantitative and qualitative data underscore the potential of hypnosis as a standalone treatment to manage stress and FNSD symptoms effectively, suggesting that it may serve as a valuable alternative in clinical practice. This study provides a basis for integrating hypnosis into therapeutic settings and highlights the need for further research to optimize its application in managing functional neurological symptoms.